Discrimination toward the Monster Character in Mary Shelley's Frankenstein Novel - Putra, Aprilian Kurnia; Ariani, Setya; Muhajir, Fatimah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This qualitative study aims to analyze discrimination aspects received by the monster character using discrimination theory. The result of this study showed that the monster character received discriminative treatment from the other characters in the form of alienation. The types of discrimination found namely direct and indirect discrimination. Direct discrimination is a type of discrimination committed by someone against another person in direct action, such as bullying, and making a person is rejected in society. On the other hand, indirect discrimination is discrimination that takes the form of a policy or attitude, which has an indirect effect on someone but also does not get equality in society. The use of two types indicates that the creature is discriminated against due to its external appearance, which is very ugly and creepy and cannot be accepted by other characters that come into contact with the discriminated monster.